Incidence and mortality of gastric cancer in Brazil and Bahia over the last 10 years (Research, Society and Development, 2022)
Introduction: Gastric cancer (GC) affects mainly males and older age groups and can lead to death. The main risk factor for the development of this tumor is infection by the H.pylori bacteria. It is known that early diagnosis and treatment results in a better prognosis for the patient. Aims: To analyze the incidence and mortality from GC in Brazil and Bahia in the last 10 years. Method: This is a descriptive, exploratory and time series study. The data collected are in the public domain and were obtained from the Population-Based Cancer Registry of the José de Alencar Gomes da Silva National Cancer Institute (INCA) and the Mortality Information System (SIM) of the Ministry of Health (DATASUS/MS) in period from 2009 to 2020. Results: There was an increase in the incidence and mortality rate from GC in Brazil in the analyzed period, with the highest incidence rate in the Southeast and South regions (average: 3,424.6 and 2,243.7 new cases/ year, respectively) and a higher mortality rate in the Southeast and Northeast regions (average: 6,593.7 and 3,164 deaths/year, respectively). Regarding age group and sex, there was a higher incidence between 60 and 69 years (average: 2,647.6 new cases/year) and a higher number of deaths between 70 and 79 years (average: 3,705.8 deaths/year) with predominance of in males in all age groups considered in Brazil, both in terms of incidence (average: 5,372.8 new cases/year) and mortality (average: 9,039.3 deaths/year). Conclusion: Based on the results, it was possible to identify the need for further investigation of gastric cancer in the health system, especially in patients with the characteristics described in this profile.